Pengaruh akuntabilitas dan transparansi lembaga zakat terhadap tingkat kepercayaan muzakki (Studi Kasus pada Lembaga Amil Zakat Masjid Jogokariyan Yogyakarta) - Rahayu, Septi Budi; Widodo, Sri; Binawati, Enita (Journal of Business and Information Systems (e-ISSN: 2685-2543), 2019)
This research was conducted to determine the transparency of zakat in the Jogokariyan Mosque in Yogyakarta. Zakat reporting is published in the Yogyakarta Jogokariyan Mosque bulletin, which is made periodically. This study aims to determine the effect of accountability and transparency of zakat institutions on the level of muzakki trust. This research is quantitative. The population taken in this study is the Jogokariyan Mosque of Yogyakarta worshipers. The sample in this study was muzakki at the Amil Zakat Institute of Jogokariyan Mosque in Yogyakarta, with 50 respondents. The type of data in this study uses primary data. Data were analyzed using validity, reliability, and multiple regression analysis. The results show that accountability and transparency have a significant effect on the level of trust in Muzakki.